Outward FDI and the Investment Development Path in Romania - SIMONA GABRIELA MASCA; VIORELA LIGIA VAIDEAN (Revista Romana de Economie, 2010)
Abstract:Our study characterizes the outward FDI phenomenon in Romania in the light of DunningÆs Investment Development Path theory, based on the relationship between a countryÆs development level and its net international investment position, that has previously been applied to most CEE countries except for ours. A series of indicators are used, concluding that, nowadays, Romania is situated in the second stage of IDP. More, we found that the IDP paradigm is generally applicable to Romania; the specific feature consists in bigger growth rates of FDI inflows than of GDP in the first stages of IDP. Some policy implications are drawn.